2015
DOI: 10.3390/min5020189
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phosphate Solubilizing Bacteria to Leach Rare Earth Elements from Monazite-Bearing Ore

Abstract: Abstract:In the present study, the feasibility to use phosphate solubilizing bacteria (PSB) to develop a biological leaching process of rare earth elements (REE) from monazite-bearing ore was determined. To predict the REE leaching capacity of bacteria, the phosphate solubilizing abilities of 10 species of PSB were determined by halo zone formation on Reyes minimal agar media supplemented with bromo cresol green together with a phosphate solubilization test in Reyes minimal liquid media as the screening studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…After a prolonged time (over 3 days) it slowed down due to the buffering effect of weak acids. Similar trends on pH profile with in-situ production of organic acids in the bioleaching of electronic waste, red mud, cracked catalysts and monazite ores have been observed in earlier studies [28,[33][34][35][36]. Reed et al [36] reported that 60% of the organic acids, mainly gluconic acid, can be produced within the initial 24 h. Using the isolated microbial culture BH1, Acinetobacter calcoaceticus GSN8; BH24, Pseudomonas frederiksbergensis 37; and A1, Talaromyces purpureogenus for producing gluconic acid were however less effective in bioleaching of REE than the bacterium Gluconobacter oxydans.…”
Section: Bio-reclamation Of Rare Earth Elementssupporting
confidence: 54%
“…After a prolonged time (over 3 days) it slowed down due to the buffering effect of weak acids. Similar trends on pH profile with in-situ production of organic acids in the bioleaching of electronic waste, red mud, cracked catalysts and monazite ores have been observed in earlier studies [28,[33][34][35][36]. Reed et al [36] reported that 60% of the organic acids, mainly gluconic acid, can be produced within the initial 24 h. Using the isolated microbial culture BH1, Acinetobacter calcoaceticus GSN8; BH24, Pseudomonas frederiksbergensis 37; and A1, Talaromyces purpureogenus for producing gluconic acid were however less effective in bioleaching of REE than the bacterium Gluconobacter oxydans.…”
Section: Bio-reclamation Of Rare Earth Elementssupporting
confidence: 54%
“…For example, Hassanien et al (2014) used heterotrophic microorganisms such as Aspergillus ficuum and Pseudomonas aeruginosa for the bioleaching of REE from Egyptian monazite, reaching high leaching efficiencies of up to 60.6% and 52.6% by A. ficuum and P. aeruginosa, respectively [33]. In a very recent study, Shin et al (2015) investigated the ability of different phosphate-solubilizing bacteria to leach REE from monazite-bearing ores. Although the bioleaching efficiencies were very low (up to 0.13% in case of Ce), the study proved the general suitability of phosphate-solubilising bacteria to degrade highly resistant monazite ores [34].…”
Section: Example: Bioleaching Of Rare Earth Elementsmentioning
confidence: 99%
“…In a very recent study, Shin et al (2015) investigated the ability of different phosphate-solubilizing bacteria to leach REE from monazite-bearing ores. Although the bioleaching efficiencies were very low (up to 0.13% in case of Ce), the study proved the general suitability of phosphate-solubilising bacteria to degrade highly resistant monazite ores [34].…”
Section: Example: Bioleaching Of Rare Earth Elementsmentioning
confidence: 99%
“…Similarly, several scholars are using cutting-edge technology to understand the irrigation and colonization of bio-heaps [110,111]. On the other hand, studies on the bioleaching from polymetallic sources and of rare elements are also part of the scientific discussion [112,113].…”
Section: Challenges and Prospective Of Biohydrometallurgymentioning
confidence: 99%